Adsorption of rare earth elements onto diatomite M45: experimental investigations and modeling with statistical physics theory (2023)
The separation of rare earth elements using diatomite M45 from aqueous solutions was studied. The experimental isotherms for the adsorption of trivalent lanthanum, cerium, and neodymium cations on this adsorbent were quantified under strongly acidic conditions (pH 2) at 298–328 K. The adsorption equilibria of these earth elements were analyzed using two statistical physics models (homogeneous and heterogeneous monolayer models). The results show that the adsorption of these ions implies a multi-ionic mechanism, which is exothermic. Si-containing functional groups are responsible for the adsorption of these rare-earth elements on the diatomite surface. A heterogeneous statistical physics model confirms that two Si-based functional groups participate in the separation of these cations. The calculated adsorption capacities at saturation follow the order: neodymium > cerium > lanthanum. Calculated interaction energies range from 28600 to 40100 J/mol, indicating physical adsorption on diatomite M45. This study demonstrates that diatomite M45 is a promising separation medium that can be used for the recovery of REEs dissolved in aqueous solutions via adsorption.